2009
DOI: 10.1021/es8035994
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Attenuation of Chlorinated Aliphatic Hydrocarbons in Eutrophic River Sediment Impacted by Discharging Polluted Groundwater

Abstract: This study explored the potential of eutrophic river sediment to attenuate the infiltration of chlorinated aliphatic hydrocarbon (CAH)-polluted groundwater discharging into the Zenne River near Brussels, Belgium. Active CAH biodegradation by reductive dechlorination in the sediment was suggested by a high dechlorination activity in microcosms containing sediment samples and the detection of dechlorination products in sediment pore water. A unique hydrogeochemical evaluation, including a delta2H and delta18O st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(81 citation statements)
references
References 15 publications
4
77
0
Order By: Relevance
“…Several processes influence CHC plume fate in the riverbed -hyporheic zone environment at the GSI (Bencala, 2000;Environment Agency, 2009). Although dilution due to surface-water mixing into discharging groundwater plumes within the hyporheic zone does not remove contaminant mass, it may reduce concentrations impacting surface waters (Conant et al, 2004;Hamonts et al, 2009). Sorption is often more significant than in the preceding aquifer as riverbed deposits are often rich in organic matter, leading to retarded transport and greater residence times (Smith and Lerner, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several processes influence CHC plume fate in the riverbed -hyporheic zone environment at the GSI (Bencala, 2000;Environment Agency, 2009). Although dilution due to surface-water mixing into discharging groundwater plumes within the hyporheic zone does not remove contaminant mass, it may reduce concentrations impacting surface waters (Conant et al, 2004;Hamonts et al, 2009). Sorption is often more significant than in the preceding aquifer as riverbed deposits are often rich in organic matter, leading to retarded transport and greater residence times (Smith and Lerner, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The groundwater samples were placed into glass bottles and maintained under 4°C conditions for transportation to the laboratory. Samples of soil and groundwater were analyzed for VOCs and SVOCs according to the procedures and methods of the Standard of Soil Quality Assessment for Exhibition Sites (Ministry of Environmental Protection of the People's Republic of China 2007) using high-performance liquid chromatography and gas chromatography (Brasseur et al 2007;Hamonts et al 2009;Ma et al 2013). Heavy metal analyses were also conducted according to the standards for inductively coupled plasma atomic emission spectrometry (Aydin and Soylak 2010).…”
Section: Sampling and Chemical Analysesmentioning
confidence: 99%
“…This could be due to the high hydraulic conductivity of 1-3 m/day at this site [222] facilitating a rapid dispersion and community succession [416]. Accordingly, the pre-biostimulation bacterial community in the stimulated wells was significantly different from the control well (Table S6.7) whereas the geochemical parameters were similar between the pre-biostimulation and control well samples and clustered closely in the PCA plot ( Figure S6.7).…”
Section: Geochemical and Microbial Dynamics: The Control Wellmentioning
confidence: 92%
“…Numerous studies reported anaerobic dechlorination of chlorinated ethenes in the groundwater surface water interaction zone from various geographical locations i.e. freshwater tidal wetlands of West Branch Canal Creek, Maryland, USA [219], Lake Michigan, USA [220], as well as streambed sediments in Angus, Ontario, Canada [221] and in Vilvoorde, Brussels, Belgium [222] without identification of responsible microorganisms. With growing interest on environmental distribution of OHRB, several 16S RNA gene-based methods were applied to track their presence in organohalide impacted or pristine sediments [48,90,186,223].…”
Section: Riverbed and Lake Sedimentsmentioning
confidence: 99%
See 1 more Smart Citation